2013
DOI: 10.1016/j.jval.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Program-Specific Cost-Effectiveness Analysis: Breast Cancer Screening Policies for a Safety-Net Program

Abstract: For the EWC program, biennial screening mammography starting at age 50 years was the most cost-effective strategy. The impact of digital mammography on life expectancy was small. Program-specific cost-effectiveness analysis can be completed in a policy-relevant time frame to assist policymakers faced with difficult program choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The analyses were based in a number of countries including the USA (n = 18 239,257,263,267,271,272,274,275,277,278,283,[289][290][291][292][293]295,298 ), the UK (n = 15 241,243,246,247,249,253,261,265,273,276,279,287,297,299,303 ), the Netherlands (n = 4 242,244,256,259 ), Hong Kong (n = 4 [304][305][306][307] ), Australia (n = 3 254,262,302 ), Italy (n = 3 245,251,252 ), Japan (n = 2 284,…”
Section: Study Overviewmentioning
confidence: 99%
“…The analyses were based in a number of countries including the USA (n = 18 239,257,263,267,271,272,274,275,277,278,283,[289][290][291][292][293]295,298 ), the UK (n = 15 241,243,246,247,249,253,261,265,273,276,279,287,297,299,303 ), the Netherlands (n = 4 242,244,256,259 ), Hong Kong (n = 4 [304][305][306][307] ), Australia (n = 3 254,262,302 ), Italy (n = 3 245,251,252 ), Japan (n = 2 284,…”
Section: Study Overviewmentioning
confidence: 99%
“…These screening approaches have shown to be more cost-effective than no screening [8,9]. The US Preventive Services Task Force (USPSTF) recommends that women between 50 and 74 years of age should receive mammography screenings every two years, while those between 21 and 65 years of age should receive a Pap smear every 3 years [10].…”
Section: Introductionmentioning
confidence: 99%
“…This will have the effect of underestimating both the effectiveness and the cost of screening; however, the difference is unlikely to be large. Previous studies have reported ICERs for digital mammography versus film of $180,333/LYG [34] and $331,000/QALY [35], suggesting that digital mammography may negatively impact the cost-effectiveness of screening programs. Lastly, our model assumes full participation and perfect adherence to screening schedules.…”
Section: Discussionmentioning
confidence: 99%